2016
DOI: 10.7196/ajhpe.2016.v8i1.757
|View full text |Cite
|
Sign up to set email alerts
|

Motivated strategies for learning and their association with academic performance of a diverse group of 1st-year medical students

Abstract: Background. Most instruments, including the well-known Motivated Strategies for Learning Questionnaire (MSLQ), have been designed in western homogeneous settings. Use of the MSLQ in health professions education is limited. Objective. To assess the MSLQ and its association with the academic performance of a heterogeneous group of 1st-year medical students. Methods. Eighty-three percent of 1st-year medical students consented to participate in this quantitative study. The MSLQ consisted of a motivation strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 13 publications
6
28
2
2
Order By: Relevance
“…The study found statistically significant correlations between academic performance and the motivation scale as well as most of its subscales, including self-efficacy for learning performance, control of learning beliefs, task value and test anxiety. These results support the results of previous studies from other fields that showed such a relationship between academic performance and motivation strategy [8], [10], [28], [29]. The subscales that showed no significant correlation were those related to goal orientation (Intrinsic goal orientation and Extrinsic goal orientation) which was in line with previous research on the same topic [28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study found statistically significant correlations between academic performance and the motivation scale as well as most of its subscales, including self-efficacy for learning performance, control of learning beliefs, task value and test anxiety. These results support the results of previous studies from other fields that showed such a relationship between academic performance and motivation strategy [8], [10], [28], [29]. The subscales that showed no significant correlation were those related to goal orientation (Intrinsic goal orientation and Extrinsic goal orientation) which was in line with previous research on the same topic [28].…”
Section: Discussionsupporting
confidence: 92%
“…These differences might be a result of the strong sex difference found in task preferences between boys and girls [37]. However, some previous results showed females having higher motivation scores than males [28], [29], [38], [39]. This variation could be related to the differences between both sexes in several factors including patterns of course-taking, achievement motivation and even educational experiences [40].…”
Section: Discussionmentioning
confidence: 99%
“…MSLQ, although generally accepted, has been also criticized as it was designed in western homogeneous settings (Hamid & Singaram, 2016). The questionnaire used in this study is focused on five categories (three regarding motivation, and two regarding learning strategies) that are relevant in the MOOC context.…”
Section: Limitationsmentioning
confidence: 99%
“…Similarly, [46] found that a strong relationship between critical thinking and academic achievement. While another study reported poor correlation between critical thinking and academic performance among first year medical students [47]. Conversely, [48] reported no correlation between academic achievement (CGPA) and critical thinking dispositions among pre-service teachers.…”
Section: Reciprocal Peer Tutoring (Rpt) Strategy For Promoting Stumentioning
confidence: 99%
“…In the present research, generic questions stems consisting of three types of questions (i=integration, c=comprehension and f=factual) by [47] were used to trigger students' critical thinking in the Facebook discussion. total of questions asked when the students became a tutor were calculated.…”
Section: Types Of Questions Used Among Students In Online Rpt Thromentioning
confidence: 99%